Genetic structuring across alternative life‐history tactics and small spatial scales in brown trout (Salmo trutta). Issue 2 (15th September 2020) - Rodger, Jessica R.; Honkanen, Hannele M.; Bradley, Caroline R.; Boylan, Patrick; Prodöhl, Paulo A.; Adams, Colin E.
Abstract: Facultative migration occurs when, in response to prevailing conditions, individuals in a population may (or may not) undertake a migration. The brown trout ( Salmo trutta ) is a species that exhibits facultative migration, where some individuals within populations may move to mainstem rivers (fluvial–adfluvial migration), lakes (lacustrine–adfluvial migration), estuaries (partial anadromy) or sea (anadromy) to feed, while others remain resident. This study attempts to separate two alternative hypotheses for the population structuring that underpins the expression of facultative migration in this species: (a) that anadromous and nonanadromous fish comprise two gene pools; (b) that individual genetic variation or individual variation in gene–environment interactions is responsible for the expression of different life‐history tactics within the same gene pool. The study design involved sampling and analyses of anadromous and nonanadromous brown trout from three independent tributary rivers known to produce (sea‐run) trout within the same catchment. Results indicate that, in all cases, population genetic divergence was linked to geographical location and not to life‐history tactics. Two genetically distinct coexisting population pairs were identified in two separate tributaries. Despite similar environmental conditions in both tributaries, the frequency of each life‐history tactic (anadromy vs. nonanadromous) within these population pairs differed significantly. The results of this study support the hypothesis that facultative migration in brown trout is likely to be driven by a quantitative threshold trait, where the threshold value varies both among populations and among individuals within populations.